Питання комплексного міждисциплінарного аналізу шарів енеоліту, ранньої бронзи та ранньозалізного часу з першого навісу Прийма І - Мацкевий, Л.; Лосик, М.; Панахид, Г. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
A settlement in cave and rock complex is situated 37 km away to the south of L’viv. The research made by I. Gunyovs’kyi and V. Ischenko affirms the most credible time when human communities lived there in a cold season and in a warm time their residence was situated at the very Dnister bank. Climate and plants were much alike modern ones. Ecological possibilities of the region provided people with building material, food supply, and raw materials for producing tools, kitchen utensils and other things. Stratiographic observations and those that study the grainy compound made by O. Alexandrovs’kyi, M. Demedyuk, and I. Gunyovs’kyi prove these statements. V. Khmelyovs’kyi and R. Smishko specify that there were deposits of qualitative stone raw material near Pryima I.